A new species of Atrachelus Amyot & Serville (Heteroptera: Reduviidae: Harpactorinae) from Argentina - Melo, María C.; Coscarón, María D.c. (Zootaxa, 2005)
A new species of Harpactorinae, Atrachelus (Phorobura) iberaensis, is described from specimens collected by the authors in Corrientes, Argentina. The male and female genitalia are figured.